Mechanisms Underlying Nutrient Interaction of Compost and Mineral Fertilizer Application in Maize (Zea mays L.) Cropping System in Ghana - Essel, Benedicta; Abaidoo, Robert Clement; Opoku, Andrews; Ewusi-Mensah, Nana (Frontiers in Soil Science, 2021)
Mechanisms underlying interactive effects of nutrient inputs on crop yields are poorly understood especially throughout sub-Saharan Africa. This research thus sought to evaluate the possible mechanisms causing the interaction effects from compost and mineral fertilizer and quantify the relative contribution(s) of the mechanisms to added benefits in grain yield. The research involved a three-year field experiment followed by a greenhouse incubation study. Both field and incubation experiments were 5 x 5 factorial arranged in Randomized Complete Block Design and Completely Randomized Design with three replications, respectively. The factors considered were five levels of mineral fertilizer (0%, 25%, 50%, 75% and 100% of 90: 60:70 kg ha-1 N: P2O5: K2O) and compost (0%, 25%, 50%, 75% and 100% of 5 Mg ha-1 compost). The mechanisms evaluated were nutrient synchrony, priming, general soil fertility improvement and balanced ratio of nutrients. The conjoint application of compost and mineral fertilizer significantly (p ≤ 0.05) influenced grain yields of maize, with 50 % RR MF + 100 % RR Co producing the highest average grain yields in 2015 and 2017 with relative average grain yield increases of 167 and 98 % over the control (no application), respectively. The conjoint application of nutrients resulted in synergistic and antagonistic interactions. Synergistic interactions were observed in the first two years of the study, followed by antagonistic interactions in the third year. Three principal components cumulatively explained 86% of the variation among the mechanisms. The mechanisms which contributed most to the added benefits were priming effect, balanced nutrient ratio and nutrient synchrony.